KEDUDUKAN HUKUM PEMBAGIAN WARIS KETIKA PENGESAHAN PERKAWINAN DAN ANAK SETELAH PEWARIS MENINGGAL DUNIA - Yopi Pebri; M. Sofyan Pulungan; Artha Febriansyah (Universitas Sriwijaya, 2024)
The purpose of this paper is to evaluate the division of inheritance in situations where marriage and child recognition take place after the testator dies. This research uses the doctrinal method, taking a statutory approach and a conceptual approach. The results show that a marriage that occurs after one of the spouses dies can still be recognized if it follows the procedure of registering the marriage at the civil registry office after obtaining a determination from the court, so that the marriage is considered valid. This is in accordance with Article 825A which states that the spouse left behind becomes the first class of heirs. Regarding the recognition of a child after the death of the father, Constitutional Court Decision No. 46/PUU-VIII/2010 allows for the legal recognition of the child, provided that it can be proven through science and technology, or other evidence that is valid according to law. Thus, the child is considered a legitimate child and becomes part of the first class of heirs together with the mother.